Studi Komitmen Organisasi Karyawan Bank: Peran Job Involvement Dan Kepuasan Kerja - Sari, Ajeng Purnama; Senen, Syamsul Hadi; Masharyono, Masharyono (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
Employees who are committed to the organization have a tendency to continue working in the organization. The loss of employee commitment means organizations lose support and loyalty from employees in achieving organizational goals. One of the companies that experienced a decline in employee organizational commitment was X Bank. The purpose of this study is to determine how much influence job involvement and job satisfaction on organizational commitment. The object in this study was employees of X bank, one of Indonesia's conventional banks. This study used saturated samples with 54 respondents. The data analysis technique used is Partial Least Squares (PLS) with computer software program smartPLS version 3.0. The results reveal that job involvement and job satisfaction influence organizational commitment. This shows that the higher job involvement and employee job satisfaction together, the higher the organizational commitment of X Bank employees.